2010
DOI: 10.1021/ie901560p
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Wood Dissolution and Regeneration of Ionic Liquids

Abstract: Three wood species, eucalyptus grandis (E. grandis), southern pine (S. pine), and Norway spruce thermomechanical pulp (N. spruce TMP) were pretreated by dissolution in the ionic liquid (IL) 1-allyl-3-methylimidazolium chloride ([AMIM]Cl). The wood was regenerated from the ionic liquid in high yield and the recycling of the ionic liquid was nearly quantitative. The lignin contents and the efficiencies of cellulase enzymatic hydrolyses of the regenerated wood were examined offering an understanding into the IL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 45 publications
9
111
0
1
Order By: Relevance
“…Ionic liquids can be tailored to dissolve the components of wood selectively (Xie et al 2009;Li et al 2010). Ionic liquids can be used to produce regenerated cellulose fiber at higher yield and better strength than conventional Lyocell fiber due to less polymer degradation (Sixta et al 2015).…”
Section: Niche Markets For Kraft Mill Biorefinery Productsmentioning
confidence: 99%
“…Ionic liquids can be tailored to dissolve the components of wood selectively (Xie et al 2009;Li et al 2010). Ionic liquids can be used to produce regenerated cellulose fiber at higher yield and better strength than conventional Lyocell fiber due to less polymer degradation (Sixta et al 2015).…”
Section: Niche Markets For Kraft Mill Biorefinery Productsmentioning
confidence: 99%
“…Z uporabo ionskih tekočin se odpira možnost za proizvodnjo celuloze pri nizkih temperaturah in atmosferskem tlaku. Visoka cena ionskih tekočin zaenkrat še onemogoča njihovo širšo uporabo v industriji (Kilpeläinen et al, 2007, Li et al, 2010.…”
Section: Typical Cations and Anions Of Ionic Liquidsunclassified
“…R-4, which was regenerated from stems submitted to 4 h of ball-milling, could be dissolved completely in 8% LiCl/DMSO to form a homogeneous and clear solution. All losses of the regenerated fraction during the dissolution-regeneration procedure were caused by the ball-milling step, which could lead to the degradation of both cellulose and lignin and thus the formation of water-soluble products that cannot be precipitated readily with water (Guerra et al 2006;Li et al 2010). However, it could be concluded that although approximately 10.0% to 25.0% of the fractions were lost during the dissolutionregeneration procedure, most of the components could be regenerated from the suspensions or solutions, which could reflect nearly all of the same characteristics of the original stem cell wall components.…”
Section: Regeneration Of Dissolved Soybean Stemmentioning
confidence: 99%